An Introduction to Labor Law - Michael Evan Gold (Cornell University Press, ILR Press, 2014)
The purpose of this book is to introduce the reader to the federal law of unions and employers. This law is composed of two major elements. The fi rst element is the National Labor Relations Act and the amendments to it. The second element is the decisions of the National Labor Relations Board and of the federal courts; these decisions interpret and apply the statutes. The statutes are long and complex, and the decisions of the Labor Board and of the courts number in the hundreds of thousands. As a result, this book cannot cover all of the law. Only the most important areas of the law are discussed, and the discussion of these areas is purposefully simplifi ed. Although all of the following statements about the law are accurate, many are incomplete. Much more could be said about every topic addressed in this book. Two types of reader are likely to benefi t from reading this book. One is the person who knows little or nothing about the law; the other is the person whose knowledge has become rusty with disuse. The former can learn, the latter can relearn, the basic principles and structures of the law. One type of reader is unlikely to benefi t from this book: the person who needs to know whether specifi c conduct, arising in a context of many other facts, is legal or illegal. Too many rules have been omitted, too many qualifi cations have gone unstated, for this book to serve this purpose. The reader who needs to know the law in a specifi c case should consult a comprehensive treatise on labor law or, better yet, a labor lawyer. Samuel Kaynard and Peter Hoffman were kind enough to read and comment on the previous editions of this book, and Kati Griffi th reviewed the revisions that are incorporated in this edition. Of course, any errors or misleading statements that may remain are the responsibility of the author